Brain immune interactions and air pollution: macrophage inhibitory factor (MIF), prion cellular protein (PrPC), Interleukin-6 (IL-6), interleukin 1 receptor antagonist (IL-1Ra), and interleukin-2 (IL-2) in cerebrospinal fluid and MIF in serum differentiate urban children exposed to severe vs. low air pollution - Calderon-Garciduenas, Lilian; Cross, Janet V.; Franco-Lira, Maricela; Aragon-Flores, Mariana; Kavanaugh, Michael; Torres-Jardon, Ricardo; Chao, Chih-kai; Thompson, Charles; Chang, Jing; Zhu, Hongtu; D'Angiulli, Amedeo (Frontiers in Neuroscience, 2013)
Mexico City Metropolitan Area children chronically exposed to high concentrations of air pollutants exhibit an early brain imbalance in genes involved in oxidative stress, inflammation, innate and adaptive immune responses along with accumulation of misfolded proteins observed in the early stages of Alzheimer and Parkinson’s diseases. A complex modulation of serum cytokines and chemokines influences children’s brain structural and gray/white matter volumetric responses to air pollution. The search for biomarkers associating systemic and CNS inflammation to brain growth and cognitive deficits in the short term and neurodegeneration in the long-term is our principal aim. We explored and compared a profile of cytokines, chemokines (Multiplexing LASER Bead Technology) and Cellular prion protein (PrPC) in normal cerebro-spinal-fluid (CSF) of urban children with high versus low air pollution exposures. PrPC and macrophage inhibitory factor (MIF) were also measured in serum. Samples from 139 children ages 11.91±4.2 y were measured. Highly exposed children exhibited significant increases in CSF MIF (p=0.002), IL6 (p=0.006), IL1ra (p=0.014), IL-2 (p=0.04), and PrPC (p=0.039) v controls. MIF serum concentrations were higher in exposed children (p=0.009). Our results suggest CSF as a MIF, IL6, IL1Ra, IL-2, and PrPC compartment that can possibly differentiate air pollution exposures in children. MIF, a key neuro-immune mediator, is a potential biomarker bridge to identify children with CNS inflammation. Fine tuning of immune-to-brain communication is crucial to neural networks appropriate functioning, thus the short and long term effects of systemic inflammation and dysregulated neural immune responses are of deep concern for millions of exposed children. Defining the linkage and the health consequences of the brain/ immune system interactions in the developing brain chronically exposed to air pollutants ought to be of pressing importance for public health.